015 How can we prevent overdoses and what works? a systematic review of interventions for non fatal poisonings. Issue 3 (1st March 2011) - Snooks, Helen; Russell, Daphne; Brown, Christine; Nair, Akshey; Moore, Chris; Lewis, Alan; Thomas, Gareth; al-Sulaiti, Mohammed; Thomas, Marie; Griffith-Noble, Faye
Abstract : Background: Deaths from opiate overdose in the UK are among the highest in Europe. Drug related deaths in Wales are not reducing. Naloxone is administered to reverse overdose by paramedics and in emergency departments. Aim: To describe interventions to treat overdoses in the pre-hospital setting and review their effectiveness. Method: 1—systematic literature search; 2—selection of comparative studies for qualitative synthesis; 3—meta-analysis of suitable studies. Results: 39 references described interventions in six categories: 1) take-home naloxone administered by peers to an overdose patient, following training; 2) CPR training for bystanders witnessing an overdose; 3) routes of naloxone administration by health professionals; 4) police attendance protocols to encourage 999 calls by peers witnessing an overdose; 5) supervised injection facilities; 6) psychosocial/educational interventions. Fifteen studies were included in the systematic review. Populations, interventions, methods and outcome were heterogeneous. Evidence of effectiveness was weak but suggested death rates may be reduced by: take-home naloxone; bystander CPR; treatment for addiction; naloxone implants. Many studies were of poor quality. Inter-study results were not comparable. Meta-analysis of effectiveness was not possible. Discussion: Naloxone is an effective treatment for the reversal of opiate overdose. Yet there is little evidence of effectiveness for interventions identified in this review, including issuing trained drug users with naloxone to treat peers. Roll out of take-home naloxone in Wales should be rigorously evaluated to assess clinical and cost effectiveness, adverse event rates and effects on drug-taking behaviour.